1989
DOI: 10.1111/j.1365-2842.1989.tb01344.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative in vitro study of visible light‐cured sealants

Abstract: The introduction of visible light polymerization in dentistry led to the development of a new generation of pit and fissure sealants. The purpose of this study was an overall evaluation of some in vitro characteristics of four new sealants (Delton LC, Helioseal, Pentra-Seal and Visioseal) in comparison with a chemically cured control (Delton). The results indicate that the monomer systems utilized in the new materials have already been used in dental polymer technology. The relatively new monomers TCDDMA/TCDMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In addition to the opacity of the sealant material affecting the depth of cure, the chemical composition of the material may have played a role as well. CQ is the photoinitator for both FluroShield and Delton LC Opaque, so it is more likely that the difference seen in their curing performance is related to the color of the material (clear vs opaque). UltraSeal XT plus does not disclose its light activator.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the opacity of the sealant material affecting the depth of cure, the chemical composition of the material may have played a role as well. CQ is the photoinitator for both FluroShield and Delton LC Opaque, so it is more likely that the difference seen in their curing performance is related to the color of the material (clear vs opaque). UltraSeal XT plus does not disclose its light activator.…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of oxygen are one of the inhibitors or retarders of the polymerization. This leads to the formation of an unpolymerized surface layer of the resin, which can be examined by microscopic techniques (Ruyter, 1981;Lekka et al, 1989;Rueggeberg & Margeson, 1990;Vallittu, 1997;Yatabe et al, 1999). The application of the reducing agent removed oxygen from the free radical, allowing the polymerization to continue.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of the surface oxygen-inhibited layer of the reline material was performed according to a modified method presented by Lekka et al (1989). The material (0·05 mL) was placed between a microscope slide and a cover slip after mixing according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Lekka et al [1989] reported similar physical properties and shear bond strengths when they compared four visible light initi ated sealants to a chemically cured control, and they found less oxygen inhibition with the light-activated sys- terns which they felt was clinically advantageous. Con versely, Atwan and Sullivan [1987] reported significantly less tensile bond strengths for a visible light activated sea lant as compared with a chemically initiated one when tested on primary and permanent extracted teeth.…”
Section: Effectiveness O F Third-generation Sealantsmentioning
confidence: 92%